How to fix a broken planet advice for surviving the 21st century - Cribb, Julian 1950- (Cambridge University Press, 2023)
Do you want to help save human civilisation? If so, this book is for you. How to Fix a Broken Planet describes the ten catastrophic risks that menace human civilisation and our planet, and what we can all do to overcome or mitigate them. It explains what must be done globally to avert each megathreat, and what each of us can do in our own lives to help preserve a habitable world. It offers the first truly integrated world plan-of-action for a more sustainable human society - and fresh hope. A must-read for anyone seeking sound practical advice on what citizens, governments, companies, and community groups can do to safeguard our future